A Dynamic Ore Reserve Calculation and Accounting System for a Stratiform Orebody - Jaczkowski B (The Australasian Institute of Mining and Metallurgy, 1977)
The lower orebody (LOB) at Chingola Divi- sion of Nchanga Consolidated Copper Mines Limited (NCCM) accounts for approximately 30 per cent of the total copper production for the company. The uniformity of the geology of the orebody lends itself readily to a computer based ore reserve calculation and accounting system. The mining units are physically defined such that a hierarchical type of com- puter file organisation can reflect the existing physical interdependencies. In 1972, a project team consisting of one representative from each of the mine planning, operational research, and computer services departments was formed to investigate and to define the technical mining requirements of the dynamic ore reserve system (DORS). The system was finally implemented in 1975ò